Striking down ‘unreasonable’ law at the behest of the judiciary: traces of judicial activism in Malaysia - Mokhtar, Khairil Azmin (2018)
The doctrine of Constitutional Supremacy in Malaysia means federal parliament and state legislature cannot make any law as they please. Any law made by federal and state legislatures shall be declared void if inconsistent with the constitution and if made outside their given power or on the ground of ultra vires. The doctrine also means the judiciary cannot declare any law unconstitutional as the judges please. They can declare law void as prescribed in the constitution. Thus, the reason to declare any law void by the court, like the power to make law by the legislatures, is also subject to the constitution. In the name of adherence to the Doctrine of Separation of Powers, judges have turned down the power declare law unconstitutional on the ground of unreasonable, arbitrary and unjust. This attitude is quite prevalent among Malaysian judges. Even among members of the judiciary it could be noticed that some judges are more inclined to be more pro-active and incline to consider constitutionality of law on the basis of reasonableness and justice. This inclination is regarded by other judges as rather dubious and even dangerous because it traverses along the thin line that borders judicial and legislative functions. In spite of the travesty some judgements have laid down rather strong foundation for the judiciary its power to strike down unreasonable law, thus reinforcing its rightful role as the defender of human rights and the guardian of the constitution. This paper examines the principles and foundations laid down by judges who go beyond traditional role of the judiciary and not restricting themselves using only conventional grounds in determining constitutionality of law.